In Vivo Phage Display as a Biomarker Discovery Tool for the Complex Neural Injury Microenvironment. Issue 2 (24th February 2021) - Martinez, Briana I.; Stabenfeldt, Sarah E.
Abstract: The heterogeneous injury pathophysiology of traumatic brain injury (TBI) is a barrier to developing highly sensitive and specific diagnostic tools. Phage display, a protein‒protein screening technique routinely used in drug development, has the potential to be a powerful biomarker discovery tool for TBI. However, analysis of these large and diverse phage libraries is a bottleneck to moving through the discovery pipeline in a timely and efficient manner. This article describes a unique discovery pipeline involving domain antibody (dAb) phage in vivo biopanning and next‐generation sequencing (NGS) analysis to identify targeting motifs that recognize distinct aspects of TBI pathology. To demonstrate this process, we conduct in vivo biopanning on the controlled cortical impact mouse model of experimental TBI at 1 and 7 days postinjury. Phage accumulation in target tissues is quantified via titers before NGS preparation and analysis. This phage display biomarker discovery pipeline for TBI successfully achieves discovery of temporally specific TBI targeting motifs and may further TBI biomarker research for other characteristics of injury. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Phage production and purification Support Protocol : Controlled cortical impact model Basic Protocol 2 : Injection and elution of phage Basic Protocol 3 : Amplicon sequencing and sequence analysis